Effect of Biourine on N Uptake and Cabbage (Brassica oleraceae L) Growth on Lowland Ultisol - Amin Nur Rohman; M. Faiz Barchia; Bambang Gonggo Murcitro (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2020)
Research on the effect of doses of cattle biourine on plant N levels and growth of cabbage (Brassica oleraceae, L) in lowland Ultisol was carried out by Desa Bakti in Marga Sakti Sebelat District, North Bengkulu Regency in October 2019 to January 2020. This study aimed to determine the dosage of cattle biourine optimal for N levels and cabbage growth in lowland ultisols. This study used a Randomized Complete Block Design (RCBD) of one factor consisting of 4 treatments and 4 replications, with the treatment dose 0 L ha-1, 1500 L ha-1, 3000 L ha-1, and 4500 L ha-1. Observation data were analyzed by Analysis of variance (ANOVA) at ? level of 5% with the Orthogonal Polynomial Test. The results of the study showed that the optimum dosage was not obtained on the variable N levels of plants and soil pH, but had a very significant effect on both of these variables. The optimum dosage obtained on the variable growth and yield of plants includes the optimum dose of 2250 L ha-1 biourine producing an average plant height of 36.14 cm age 45 dap, the optimum dose of 2200 L ha-1 of biourine produces an average plant height of 37.87 cm age 60 dap, optimum dose of biourine 1250 L ha-1 produces an average biomass fresh weigh 1.33 kg, the optimum dose of biourine 1666.67 L ha-1 produces an average head weight of 0.83 kg, and optimum dose of biourine 2000 L ha-1 produces average head diameter of 15.36 cm.